Study of Macrozoobenthic Diversity in the New River Flow of Pinang City, Labuhan Batu Selatan - Leli Febriani; Arman Harahap (Budapest International Research and Critics University, 2021)
Benthos is an organism that lives on the bottom of the waters, both in the form of animals and plants, living on the surface and on the bottom of the waters. This study aims to determine the diversity of macrozoobenthic species in the Barumun River, Pinang City. The research starts from December 2020 to February 2021. Macrozoobenthic sampling using Surber net and Ekman Grab based on substrate differences in the riverbed. Macrozoobenthos found in the Barumun River in Pinang City consists of two phyla, namely Arthropoda and Molluscs. The phylum Arthropods found are from the class of insects belonging to the genera Hydropsyche, Polycentropus, psephenus, Dryops, Anthopotamu, Acroneuria and Triops. The phylum Molluscs found were from the Bilvavia class which belonged to the Corbicula genus and from the Gastropod class of the Genera Melanoides and Melanatria. The highest macrozoobenthic abudance at each station was Polycentropus (65,67 ind L) and Potadoma (265,67 ind L). The highest macrozoobenthic abudance found was Melanatria at (633,67 ind L) based on the vulnerability index value (H) (2,087 – 1,003) dominance index (C) (0133 -0,389) and evenness index (E) (0,365-0,603) Barumun River Kota Pinang is included in the good condition category with high species diversity. The physical and chemical factors of the waters are able to support macrozoobenthic life.